Svetniška imena in njihovo prevajanje - Štavbar, Simona (2013)
Saints Names and Their Translations. The monograph is a synthesis of translation and linguistics - onomastics. The author has collected more than four hundred names of saints who are culturally renowned in Slovenia and added corresponding names in English and German. She justified when and why saintly names need to be translated and highlighted many cases of mistranslation. The work is a valuable and extremely useful contribution to the field of translation - in theoretical as well as practical terms. It is also indirectly relevant to other fields such as religion, culture, history, music, tourism and more. A glossary of council names, regional and local variants of council names, and officially accepted variants of them are added to assist translators. The text excels in introductions, sources, literature, and footnotes covering linguists, onomastics, theologians, ethnologists, historians, geographers, and other researchers who - each from their professional perspective, dealt with saints and the saints' names. The work can serve as a guide for translators of historical, tourist, religious and many other texts where secular names appear. It can also be a useful didactic resource in teaching translation at higher education level.